Protein supplementation improves physical performance in frail elderly people: a randomized, double-blind, placebo-controlled trial - Tieland, Michael; van de Rest, Ondine; Dirks, Marlou L; van der Zwaluw, Nikita; Mensink, Marco; van Loon, Luc J C; de Groot, Lisette C P G M (Journal of the American Medical Directors Association, 2012)
Protein supplementation has been proposed as an effective dietary strategy to increase skeletal muscle mass and improve physical performance in frail elderly people. Our objective was to assess the impact of 24 weeks of dietary protein supplementation on muscle mass, strength, and physical performance in frail elderly people. A total of 65 frail elderly subjects were included and randomly allocated to either daily protein or placebo supplementation (15 g protein at breakfast and lunch). Skeletal muscle mass (DXA), muscle fiber size (muscle biopsy), strength (1-RM), and physical performance (SPPB) were assessed at baseline, and after 12 and 24 weeks of dietary intervention. Skeletal muscle mass did not change in the protein- (from 45.8 ± 1.7 to 45.8 ± 1.7 kg) or placebo-supplemented group (from 46.7 ± 1.7 to 46.6 ± 1.7 kg) following 24 weeks of intervention (P > .05). In accordance, type I and II muscle fiber size did not change over time (P > .05). Muscle strength increased significantly in both groups (P < .01), with leg extension strength tending to increase to a greater extent in the protein (57 ± 5 to 68 ± 5 kg) compared with the placebo group (57 ± 5 to 63 ± 5 kg) (treatment × time interaction effect: P = .059). Physical performance improved significantly from 8.9 ± 0.6 to 10.0 ± 0.6 points in the protein group and did not change in the placebo group (from 7.8 ± 0.6 to 7.9 ± 0.6 points) (treatment × time interaction effect: P = .02). Dietary protein supplementation improves physical performance, but does not increase skeletal muscle mass in frail elderly people.